Corneal targeted fenticonazole nitrate-loaded novasomes for the management of ocular candidiasis: Preparation, in vitro characterization, ex vivo and in vivo assessments - Sadek Ahmed; Maha M. Amin; Sarah Mohamed El-Korany; Sinar Sayed (Taylor & Francis Group, 2022)
The purpose of this manuscript was to develop and optimize Fenticonazole Nitrate (FTN)-loaded novasomes aiming to enhance drug corneal penetration and to improve its antifungal activity. Ethanol injection was used to formulate FTN-loaded novasomes adopting a central composite design. The researched factors were: stearic acid concentration (g%) (A), span 80: drug ratio (B) and cholesterol amount (mg) (C), and their effects on percent entrapment efficiency (EE%), particle size (PS), poly-dispersity index (PDI), zeta potential (ZP), and in vitro drug release after 8 hours (Q8h) were studied. Numerical optimization by Design-Expert® software was employed to select the optimum formula in respect to highest EE%, ZP (as absolute value), and Q8h >80% and lowest PS and PDI. Additional evaluation of the optimum formula was accomplished by short term stability study, effect of gamma sterilization, determination of Minimal Inhibitory Concentration and ex vivo corneal permeation study. The in vivo evaluation of the optimum formula was done to ensure its safety via in vivo ocular irritancy and in vivo corneal tolerance studies. Also, the efficacy was confirmed through in vivo corneal uptake study and susceptibility test. The optimum formula with the highest desirability value (0.738) showed EE% (94.31%), PS (197.05 nm), ZP (-66.95 mV) and Q8h (85.33%). It revealed to be safe, with augmented corneal permeation (527.98 µg/cm2) that leads to higher antifungal activity. The above results confirmed the validity of novasomes to improve the corneal permeation and antifungal activity of Fenticonazole Nitrate.